Mehmed Sâî’nin İbn Meşîş Salavâtı şerhi : metin-inceleme - Erkan, İrem Nebile (My University, 2025)
Mehmed Sâî’nin İbn Meşîş Salavâtı şerhi : metin-inceleme Bu çalışma, Abdüsselâm b. Meşîş el-Hasenî’nin (ö. 625/ 1228) salavâtı üzerine Mehmed Sâî b. İsmâil’in yazdığı şerhi konu almaktadır. XIX. yüzyıl Osmanlı Anadolu’sunda Manisa çevresinde yaşamış olan Sâî’nin Şerh-i Salavât-ı Meşîşiyye isimli eserini ve tasavvuf literatüründeki yerini inceleyen çalışma üç bölümden oluşmaktadır. “Mehmed Sâî’nin Hayatı ve Eserleri” başlıklı birinci bölümde Sâî’nin hayatına ve çevresine ilişkin veriler değerlendirilmiş, İbn Meşîş salavâtıyla hac maksadıyla gittiği Hicaz’da karşılaşması üzerinde durulmuştur. “Şerh-i Salavât-ı Meşîşiyye’nin İçeriği” başlıklı ikinci bölümün ilk kısmında Sâî’nin şerhinde kullandığı kaynaklar doğrudan ve dolaylı olarak sınıflandırılarak incelenmiş ve şerhte XIX. yüzyıl matbûâtının etkisi gösterilmiştir. İkinci kısımda ise İsmail Hakkı Bursevî’nin (ö. 1137/ 1725) eserleriyle kurduğu ilişki, XVIII. yüzyıl İbn Meşîş salavâtı şârihlerinden Mustafa b. Kemâleddin el- Bekrî (ö. 1162/ 1749) ile Abdullah b. İbrâhim el-Mîrganî’nin (ö. 1207/ 1793) eserlerinin etkisi ve Nakşibendî âdâb metinlerinin eser üzerindeki izleri incelenmiştir. Ardından metnin nüsha bilgileri ve neşir ilkeleri üzerinde durulmuş ve “Şerh-i Salavât-ı Meşîşiyye –Metin–” başlıklı üçüncü bölümde şerhin çeviri yazısı sunulmuştur.

Mehmed Sāī and His Commentary on the Salat al-Mashīshiyya : textual analysis and study This study explores the commentary composed by Mehmed Sāī b. Ismāīl on the Salawāt of Abd al-Salām b. Mashīsh al-Ḥasanī (d. 625/ 1228). Centering on Sāī’s work, Sharh-i Salawāt-i Mashīshiyya, and its place within the broader Sufi intellectual and literary tradition, the study is organized into three main chapters. The first chapter, “The Life and Works of Mehmed Sāī,” offers a biographical overview of Sāī, a nineteenth-century Ottoman scholar active in the Manisa region of Anatolia. It situates him within his historical and cultural milieu and discusses his encounter with Ibn Mashīsh’s salawāt during his pilgrimage to the Hijaz. The second chapter, “The Content of Sharh-i Salawāt-i Mashīshiyya,” opens with an examination of the sources Sāī draws upon, distinguishing between direct and indirect influences, and highlighting the impact of nineteenth-century Ottoman print culture on his work. The chapter then analyzes Sāī’s intellectual engagement with the writings of Ismāīl Haqqī Bursevī (d. 1137/ 1725), traces the influence of earlier eighteenth-century commentators on Ibn Mashīsh’s ṣalawāt —notably Mustafā b. Kamāleddīn al-Bakrī (d. 1162/ 1749) and Abd Allāh b. Ibrāhīm al-Mīrghanī (d. 1207/ 1793)— and identifies the presence of Naqshbandī ādāb (spiritual etiquette) traditions within the commentary. The final chapter outlines the manuscript tradition and editorial methodology employed in preparing the text. Under the title “Sharh-i Salawāt-i Mashīshiyya– Text –,” it presents the transliterated edition of Sāī’s commentary, offering scholars a critical resource for further study of Ottoman Sufi exegetical literature.
Mehmed Sāī and His Commentary on the Salat al-Mashīshiyya : textual analysis and study
Keywords: Abd al-Salām ibn Mashīsh; Abd Allāh b; Abdullah; Abdüsselâm b. Meşîş; b. İbrâhim el-Mîrganî; Bursawī; Ibrāhīm al-Mīrganī; Ismāīl Haqqī; İsmâil Hakkı Bursevî; Mehmed; Mehmed Sāī b. Ismāīl; Mustafa b. Kemâleddîn el-Bekrî; Mustafa ibn Kamāl al-Dīn al-Bakrī; Sâî b. İsmâil; Shādhiliyya; Sufi Literature; Sufism; Şâzeliyye; Tasavvuf; Tasavvuf Tarihi Literatürü